2021
DOI: 10.3389/fncir.2021.648487
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Dissection of a Simple Neural Circuit: Functional Domains of the Mauthner-Cell During Habituation

Abstract: Sensorimotor integration is a pivotal feature of the nervous system for ensuring a coordinated motor response to external stimuli. In essence, such neural circuits can optimize behavioral performance based on the saliency of environmental cues. In zebrafish, habituation of the acoustic startle response (ASR) is a simple behavior integrated into the startle command neurons, called the Mauthner cells. Whereas the essential neuronal components that regulate the startle response have been identified, the principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(58 reference statements)
3
6
0
Order By: Relevance
“…SLC latency shortens after ablating feedforward glycinergic inputs to the Mauthner neuron, pharmacological inhibition of glycine receptors, and cacna2d3 mutation, which all also reduce SLC habituation [75][76][77][78] . In contrast, the NMDA antagonist l-7,01,324 disrupts habituation through the feed-forward excitatory spiral fiber pathway with no impact on SLC latency 79 , consistent with our transgenic dissociation of SLC habituation and latency. Together these suggest the AP2 complex could both enhance the activity of the feed-forward inhibitory glycinergic pathway to regulate acoustically-evoked SLC latency and regulate the feed-forward excitatory pathway to modulate habituation learning.…”
Section: The Ap2 Complex Modulates Multiple Aspects Of Acoustically-e...supporting
confidence: 86%
“…SLC latency shortens after ablating feedforward glycinergic inputs to the Mauthner neuron, pharmacological inhibition of glycine receptors, and cacna2d3 mutation, which all also reduce SLC habituation [75][76][77][78] . In contrast, the NMDA antagonist l-7,01,324 disrupts habituation through the feed-forward excitatory spiral fiber pathway with no impact on SLC latency 79 , consistent with our transgenic dissociation of SLC habituation and latency. Together these suggest the AP2 complex could both enhance the activity of the feed-forward inhibitory glycinergic pathway to regulate acoustically-evoked SLC latency and regulate the feed-forward excitatory pathway to modulate habituation learning.…”
Section: The Ap2 Complex Modulates Multiple Aspects Of Acoustically-e...supporting
confidence: 86%
“…We found no significant difference in either the percentage of elicited startle responses or the ratio of short-latency escapes (Figure S6). To assess target engagement of EvoSiR4 in the brain, we imaged the transgenic Tol056 zebrafish strain, which express eGFP in the Mauthner-neurons in the hindbrain responsible for the initiation of the short-latency escape response using confocal microscopy . In agreement with the behavioral data, we found no significant EvoSiR label, indicating that the bath-applied probe does not enter the zebrafish CNS (Figure S6).…”
Section: Resultssupporting
confidence: 88%
“…We previously showed that Hip14 can palmitoylate Kv1.1 and that it regulates its localization to the spiral fiber terminals [ 28 ]. Moreover spiral fibers are known to undergo plasticity during habituation learning [ 37 ]. Interestingly, these neurons were not reliably identified as showing differential activity in MK-801 or Butaclamol-treated animals (Module 1).…”
Section: Discussionmentioning
confidence: 99%